Effects of Exercise Frequency with Complex Contrast Training on Measures of Physical Fitness in Active Adult Males - Gopal Kumar; Vivek Pandey; Rohit K. Thapa; Anthony Weldon; Urs Granacher; Rodrigo Ramirez-Campillo (MDPI AG, 2023)
Complex contrast training (CCT) is an exercise modality that utilizes both high-load resistance activity and low-load plyometric activity in a set-by-set fashion within a single exercise session. Such a combination of exercises targets multiple aspects of the force-velocity curve and may thus lead to improvement of various components of physical fitness. However, no previous study has attempted to compare the effects of load-equated two vs. three CCT sessions per week on measures of physical fitness. Forty-five male participants aged 21.4 ± 2.0 years were randomly assigned to either two weekly CCT sessions (CCT-2; n = 15), three weekly CCT sessions (CCT-3; n = 15), or an active control group (CG; n = 15). Selected measures of physical fitness were assessed pre- and post-six weeks of training. The tests included the assessment of 15 and 30 m linear sprint speeds, upper (medicine ball throw) and lower limb muscle power (standing long jump and countermovement jump with arm thrust), muscle strength (isokinetic peak knee extensor/flexor torque), and change-of-direction speed (modified agility T-test (MAT)). Significant group-time interactions were observed for all dependent variables (all p < 0.001, ɳp2 = 0.51-0.78) using ANOVA. Post hoc tests indicated significant performance improvements for the CCT-2 and CCT3 groups for all dependent variables (Hedge's g = 0.28-3.26, %Δ = 2.4-16.7), including the 15 and 30 m linear sprint speeds (p < 0.001), medicine ball throw (p < 0.001), standing long jump (p < 0.001), countermovement jump with arm thrust (p < 0.001), right leg knee extensor (p < 0.001) and flexor peak torque (p < 0.001), left leg knee extensor (p < 0.001) and flexor peak torque (p < 0.001), and change-of-direction speed (p < 0.001). The CCT-3 group showed greater improvements in MAT compared to the CCT-2 group (g = 3.26 vs. 0.70, p < 0.001). In conclusion, compared to active controls, the load-equated CCT-2 and CCT-3 programs provided similar effects on measures of physical fitness in active adult males. However, an athlete's goal is to improve their MAT score, the CCT-3 program may elicit greater improvements compared with the CCT-2 program.